Analisis Financial Management Behavior Mahasiswa FEB Penerima KIP-K UPN “Veteran” Jawa Timur - Arif Wicaksono, Tegar Mohamad; Takarini, Nurjanti (Al-Buhuts, 2024)
This study aims to determine the influence of financial knowledge, financial attitude, locus of control, and lifestyle on financial management behavior. The study population was FEB UPN "Veteran" East Java students who received KIP-K. By using the simple random sampling method, and using the Slovin formula, 84 respondents were generated. Primary data obtained from the googleform questionnaire were used in this study. The analysis method used was Partial Least Square (PLS). The results showed that financial knowledge, financial attitude, locus of control, and lifestyle had a positive effect on financial management behavior.